2009
DOI: 10.1590/s0001-37652009000300010
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and secretory function of white adipose tissue: effect of dietary fat

Abstract: Approximately 40% of the total energy consumed by western populations is represented by lipids, most of them being ingested as triacylglycerols and phospholipids. The focus of this review is to analyze the effect of the type of dietary fat on white adipose tissue metabolism and secretory function, particularly on haptoglobin, TNF-α, plasminogen activator inhibitor-1 and adiponectin secretion. Previous studies have demonstrated that the duration of the exposure to the high-fat feeding, amount of fatty acid pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 124 publications
0
19
0
3
Order By: Relevance
“…An alteration in any of the related pathways reduces insulin's effectiveness and leads to the insulin-resistance and glucose intolerance associated with advancing age [35]. Adiponectin is an adipokines secreted by the adipose tissue, and has been suggested to be an important regulator of insulin action, thereby possibly linking adiposity and insulin sensitivity [36]. …”
Section: Discussionmentioning
confidence: 99%
“…An alteration in any of the related pathways reduces insulin's effectiveness and leads to the insulin-resistance and glucose intolerance associated with advancing age [35]. Adiponectin is an adipokines secreted by the adipose tissue, and has been suggested to be an important regulator of insulin action, thereby possibly linking adiposity and insulin sensitivity [36]. …”
Section: Discussionmentioning
confidence: 99%
“…Several research groups have reported that consumption of saturated fat suppresses production of the insulin-sensitizing adipokine adiponectin in white adipose tissue of humans and rodents (reviewed in [42], [43]. Furthermore, Fernandez-Real et al demonstrated a negative correlation between palmitate and circulating adiponectin in human serum [44].…”
Section: Discussionmentioning
confidence: 99%
“…leptin and adiponectin), glucose tolerance and insulin sensitivity (adiponectin and resistin) and classical cytokines (e.g. TNF-α, interleukin-6 and 10) [3, 4]. …”
Section: Introductionmentioning
confidence: 99%